Penerapan Metode Lean Six Sigma (DMAIC) untuk Meningkatkan Produktivitas Pengelasan Plat Silinder - Fadyla Indra Kusuma; Hafidz Akbar Halim; Ade Nurul Hidayat (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
One of the key processes in the production of APAR cylinders is the welding of cylindrical plates, which is carried out using a Longitudinal Welding Cylinder machine and the CO₂ welding method. However, in practice, operators face several challenges, mainly due to the number of process steps that do not significantly contribute to the quantity or quality of the output, resulting in reduced productivity. This study aims to improve the productivity of the welding process through a series of improvements. The methods used include data analysis and root cause identification through the Overall Equipment Effectiveness (OEE) approach and Lean Six Sigma using the DMAIC stages (Define, Measure, Analyze, Improve, Control). Based on the Define stage, the initial OEE value was 67.49%, which is still far below the world-class standard of 85%. In the Measure stage, Pareto analysis revealed that the largest downtime (2,097 minutes or 40%) was caused by cycle time issues. Further analysis showed that activities such as material setup, additional plate placement, and additional plate cutting (totaling 85 seconds) could still be optimized. During the Improve stage, modifications were made, such as eliminating the additional plate cutting process and adding a stopper to ensure accurate welding alignment. These improvements successfully reduced the cycle time from 180 seconds to 120 seconds, thereby decreasing downtime and increasing the OEE value to 76.12%.